1983
DOI: 10.1128/iai.41.3.1340-1351.1983
|View full text |Cite
|
Sign up to set email alerts
|

Attaching and effacing activities of rabbit and human enteropathogenic Escherichia coli in pig and rabbit intestines

Abstract: Three strains of enteropathogenic Escherichia coli (EPEC), originally isolated from humans and previously shown to cause diarrhea in human volunteers by unknown mechanisms, and one rabbit EPEC strain were shown to attach intimately to and efface microvilli and cytoplasm from intestinal epithelial cells in both the pig and rabbit intestine. The attaching and effacing activities of these EPEC were demonstrable by light microscopic examination of routine histological sections and by transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
415
0
23

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 796 publications
(451 citation statements)
references
References 17 publications
11
415
0
23
Order By: Relevance
“…JPN 15 (pMAR7) EPEC strain we observed that the localized circumscribed clusters characteristic of EPEC adherence [32,43,541 occured only in differentiated enterocyte-like HT-29 glc-/+. Moreover, we observed that the cluster-localized binding of EPEC bacteria to Caco-2 cells, which spontaneously differentiate in culture [5], developed in parallel with cell differentiation, disclosed by immunofluorescence labeling of sucrase-isomaltase, a differentiation-associated brush border hydrolase [55].…”
Section: Work Presented In This Communication Analyses the Cellassocimentioning
confidence: 75%
“…JPN 15 (pMAR7) EPEC strain we observed that the localized circumscribed clusters characteristic of EPEC adherence [32,43,541 occured only in differentiated enterocyte-like HT-29 glc-/+. Moreover, we observed that the cluster-localized binding of EPEC bacteria to Caco-2 cells, which spontaneously differentiate in culture [5], developed in parallel with cell differentiation, disclosed by immunofluorescence labeling of sucrase-isomaltase, a differentiation-associated brush border hydrolase [55].…”
Section: Work Presented In This Communication Analyses the Cellassocimentioning
confidence: 75%
“…Diarrhea represents an increasing and recurrent problem in young calves, from 1 week up to 12 weeks of age, especially in suckling beef calves, in farms where the neonatal diarrhea problems have regressed thanks mainly to vaccination and higher hygiene standards. Among the possible infectious agents, the`attaching and effacing' strains of E. coli (AEEC; Moon et al, 1983) have been associated with diarrhea and dysentery in calves up to 2 months of age (Butler and Clarke, 1994;Mainil et al, 1993). However no large scale epidemiological study has been carried out to verify this association mainly because of the difficulty in the diagnosis of the AEEC.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, attaching and effacing E. coli (AEEC) (Moon et al, 1983) have been implicated in diarrhea and dysentery mostly in 2 to 8-week old calves (Chanter et al, 1984;Mainil et al, 1993).``Attaching and effacing'' was the term first used by Moon et al (1983) to describe an intestinal lesion produced by E. coli:`attaching' indicates the intimate attachment of bacteria to the enterocyte;`effacing' signifies the localized effacement of brush border microvilli. Such a lesion appears when enteropathogenic E. coli (EPEC) or enterohaemorrhagic E. coli (EHEC) infect their host.…”
Section: Introductionmentioning
confidence: 99%
“…C. parvum and coronavirus were identified in one additional calf. Histopathologic lesions consistent with the attaching and effacing phenotype (Moon et al, 1983;Hall et al, 1985Hall et al, , 1990Chanter et al, 1984Chanter et al, , 1986Moxley and Francis, 1986;Pospischil et al, 1987;Janke et al, 1990) were detected in 10 calves. The lesion was detected in the colon only of six calves and in the ileum and colon of four calves.…”
Section: Postmortem Examination Data and Concurrent Infectionsmentioning
confidence: 96%
“…Calf strains of Escherichia coli possessing the eae gene and having the capacity to induce the attaching and effacing lesion are designated as attaching and effacing E. coli (AEEC) (Moon et al, 1983). Intimin, a 94 kDa outer membrane protein encoded by the eae gene, mediates adherence of AEEC to intestinal epithelial cells; an event critical for the formation of the attaching and effacing lesion (Jerse and Kaper, 1991;Donnenberg and Kaper, 1992).…”
Section: Introductionmentioning
confidence: 99%